INCOME AND ADDED VALUE OF BROWN SUGAR BUSINESS IN LEBONG REGENCY, BENGKULU PROVINCE - Putri Suci Asriani; Bambang Sumantri; Marthalinda Dwi Putri; Nadia Putri Khairunnisa (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2022)
Lebong Tengah District is a brown sugar producing center in Lebong Regency, Bengkulu Province. The production process and marketing channels are factors that determine the price and quality of brown sugar reaching consumers. The purpose of the study was to determine the level of income and added value of sap obtained by brown sugar craftsmen. The research was conducted in the village of Danau Liang, Central Lebong District, Lebong Regency. The research was conducted using a survey method. The research population is brown sugar craftsmen who also act as sap seekers from the palm trees they have in the research area. Determination of the number of samples was carried out using the formula proposed by Nazir (1988) so that the number of samples was determined to be 45 people. Based on the results of the study, it can be seen that for every one-time production process (PP) the income obtained by brown sugar craftsmen is Rp. 320,333.33 with production costs incurred of Rp.249,348.78 so the income earned by brown sugar craftsmen is Rp. 70,984.55. The added value obtained from processing 100.20 liters of sap with the price of raw sap of Rp. 1,800.00 to become 21 kg of brown sugar is Rp. 712.00/Kg. In terms of processing sap into brown sugar, it is very important to pay attention to the costs incurred for the production process by further optimizing production costs and maximizing brown sugar production, the craftsmen will get greater profits from this brown sugar processing..